Rate of Post-Operative Wound Infection and Mortality Related with Surgery among Patients presented with Spinal Cord Lesions among Bangladeshi Population: A Retrospective Study (Bangladesh Journal of Medical Microbiology, 2025)
Background: Spinal cord lesions are operated for the excision as well as for treatment purpose.Objective: The purpose of the present study was to post-operative infection and mortality related with surgery among patients presented with spinal cord lesions.Methodology: This retrospective cross-sectional study was conducted in the Department of Neurosurgical spine at National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from January 2022 to December 2022 for a period of one year. All the patients with any age presented with spinal complain like pain, movement restriction or bony destruction were selected for this study. The patients with traumatic injury to the spine were excluded from this study. The details of the patients were recorded for this study. The management of the patients were performed according to the treatment protocol of this institute.Results: A total number of 463 patients were admitted in the Department of Neurosurgery Spine during the study period. The mean age group of this study population was 35.2±15.3 years with the age range of 21 to 71 years. The male and female ratio was 6.6:1. PLID & Lumber Canal Stenosis was the most common disease among all surgical procedure which was 143(40.1%) cases. The rate of post-operative infection was 18(5.0%) cases among the 357 surgical cases of spinal lesion. The most common isolated bacteria from wound infection were Pseudomonas species which was 10(55.6%) cases followed by Klebsiella pneumoniae and Staphylococcus aureus which were 5(27.8%) cases and 2(11.1%) cases respectively.Conclusion: In conclusion post-operative infection is not uncommon among the spinal surgery with the predominant of Pseudomonas species. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):70-75